Skewness preferences: Evidence from online poker - Markus Dertwinkel-Kalt; Johannes Kasinger; Dmitrij Schneider (Leibniz Institute for Financial Research SAFE, 2022)
We investigate what statistical properties drive risk-taking in a large set of observational panel data on online poker games (n=4,450,585). Each observation refers to a choice between a safe "insurance" option and a binary lottery of winning or losing the game. Our setting offers a real-world choice situation with substantial incentives where probability distributions are simple, transparent, and known to the individuals. We find that individuals reveal a strong and robust preference for skewness. The effect of skewness is most pronounced among experienced and losing players but remains highly significant for winning players, in contrast to the variance effect.
Keywords: D01; D81; G40; 330; Online Poker; Risk Attitudes; Risk Preferences; Choice under Risk